2017
DOI: 10.1007/s10495-017-1355-5
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 70 protects cardiomyocytes through suppressing SUMOylation and nucleus translocation of phosphorylated eukaryotic elongation factor 2 during myocardial ischemia and reperfusion

Abstract: Myocardial ischemia and reperfusion (MIR) results in cardiomyocyte apoptosis with severe outcomes, which blocks cardiac tissue recovering from myocardial ischemia diseases. Heat shock protein 70 (HSP70) is one of protective molecule chaperones which could regulate the nucleus translocation of other proteins. In addition, eukaryotic elongation factor 2 (eEF2), which modulates protein translation process, is vital to the recovery of heart during MIR. However, the relationship between HSP70 and eEF2 and its effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Some reports demonstrated that increased Hsp-70 expression in lungs protects alveolar epithelial cells against apoptosis and antagonizes the hyperoxia injury (14,17,18). Increasing evidence suggests that overexpression of Hsp-70 alleviates cell apoptosis via the mitogen-activated protein kinase (MAPK) signaling pathway, and exogenous extracellular Hsp-70 can prevent caspase-3 activation to inhibit cell apoptosis via Toll-like receptors and TRIF-nuclear factor kappa B pathway (14,(27)(28)(29). The results indicate that administration of recombinant human Hsp-70 with primary epithelial cells derived from TA significantly inhibited decreased respiratory epithelial cell apoptosis by hydrogen peroxideinduced oxidative stress; therefore, targeting Hsp-70 is possibly a good strategy to develop anti-oxidative therapeutics in patients with BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports demonstrated that increased Hsp-70 expression in lungs protects alveolar epithelial cells against apoptosis and antagonizes the hyperoxia injury (14,17,18). Increasing evidence suggests that overexpression of Hsp-70 alleviates cell apoptosis via the mitogen-activated protein kinase (MAPK) signaling pathway, and exogenous extracellular Hsp-70 can prevent caspase-3 activation to inhibit cell apoptosis via Toll-like receptors and TRIF-nuclear factor kappa B pathway (14,(27)(28)(29). The results indicate that administration of recombinant human Hsp-70 with primary epithelial cells derived from TA significantly inhibited decreased respiratory epithelial cell apoptosis by hydrogen peroxideinduced oxidative stress; therefore, targeting Hsp-70 is possibly a good strategy to develop anti-oxidative therapeutics in patients with BPD.…”
Section: Discussionmentioning
confidence: 99%
“…These changes facilitate the translocation of eEF2 into the nucleus and subsequently induce deformation and instability of the nucleus, thereby inducing cardiomyocyte apoptosis (C. Zhang, Liu, Zhang, et al, ). It was demonstrated that HSP70 bound to the C‐terminal fragment and the SUMO2/3‐ylation interaction motifs of eEF2, which subsequently contributed to inhibited phosphorylation and SUMOylation of eEF2, respectively (C. Zhang, Liu, Miao, et al, ). These functions of HSP70 inhibited the activation of eEF2 and suppressed the translocation of eEF2 into the nucleus, thus inhibiting eEF2‐induced cardiomyocyte apoptosis in I/R hearts (C. Zhang, Liu, Miao, et al, ).…”
Section: Hsp70: Related Mechanisms Involved In Myocardial I/rmentioning
confidence: 99%
“…Mine et al 60 added that HSP mRNA enhanced in leucocytes resulting from intestinal I–R. Hsp70 expression was also raised following I–R in rat kidney and heart 61 , 62 .…”
Section: Discussionmentioning
confidence: 99%